Potentiality of Banana and Pumpkin Fruits Residues as a Cheap Source of Valuable Nutrients - Mahmud, MR; Hossain, MS; Shuvo, SD; Reza, MSA; Abedin, MZ (Journal of Environmental Science and Natural Resources, 2022)
Banana peel and pumpkin seeds are under-utilized by-products or wastes of the household and food processing industry but these could be rich in valuable nutritive compounds. Having a scientific database on the chemical and proximate analysis of the plants cultivated in the particular region would be helpful to the food product manufacturer, educator, researcher, public health personnel, policymaker, and population under food stress. Literature indicates that the nutritional and chemical composition of these under-utilized materials has not been characterized previously. The present study was designed to examine the nutritional, antioxidants, vitamin C, total phenolic and flavonoid contents of peels and seeds flour of selected fruits. Nutritional analysis reveals that the peel flour of Musa acuminata is rich in crude fiber 14.13%, carbohydrate 60.38%, and seed flour of Cucurbita maxima is rich in protein 30.05%, fat 43.81%, dietary fiber 13.81%. BPF showed more antioxidant activity (86.8%), total phenolic and flavonoid content than PSF, which is rich in vitamin C content (9.23 mg/100gm). Industrial by-products can be processed into value-added products such as flour that is more easily stored for further uses. By-product flour can easily include in food formulations due to its excellent nutritional qualities. Optimization of its use is beneficial in terms of nutritional and economical points of view. Environ. Sci. & Natural Resources, 13(1&2): 87-93, 2020